Intracranial hematoma and abscess after neuraxial analgesia and anesthesia: a review of the literature describing 297 cases. Issue 4 (13th January 2021) - Bos, Elke ME; van der Lee, Koen; Haumann, Johan; de Quelerij, Marcel; Vandertop, W Peter; Kalkman, Cor J; Hollmann, Markus W; Lirk, Philipp
Abstract : Background: Besides spinal complications, intracranial hematoma or abscess may occur after neuraxial block. Risk factors and outcome remain unclear. Objective: This review evaluates characteristics, treatment and recovery of patients with intracranial complications after neuraxial block. Evidence review: We systematically searched MEDLINE, Embase and the Cochrane Library from their inception to May 2020 for case reports/series, cohort studies and reviews of intracranial hematoma or abscess associated with neuraxial block. Quality of evidence was assessed using the critical appraisal of a case study checklist by Crombie. Findings: We analyzed 232 reports, including 291 patients with hematoma and six patients with abscess/empyema. The major part of included studies comprised single case reports with a high risk of bias. Of the patients with hematoma, 48% concerned obstetric patients, the remainder received neuraxial block for various perioperative indications or pain management. Prior dural puncture was reported in 81%, either intended (eg, spinal anesthesia) or unintended (eg, complicated epidural catheter placement). Headache was described in 217 patients; in 101 patients, symptoms resembled postdural puncture headache (PDPH). After treatment, 11% had partial or no recovery and 8% died, indicating the severity of this complication. Intracranial abscess after neuraxial block is seldom reported; six reports were found. Conclusion: Diagnosis of intracranial hematoma is often missed initially, as headache is assumed to be caused by cerebrospinal hypotension due to cerebrospinal fluid leakage, known as PDPH. Prolonged headache without improvement, worsening symptoms despite treatment or epidural blood patch, change of headache from postural to non-postural or new neurological signs should alert physicians to alternative diagnoses.